The Effects of Glucagon-Like Peptide-1 Receptor Agonists of Liraglutide on Bone Turnover Makers Among Type 2 Diabetes Mellitus Patients: A Meta-Analysis of Randomized Controlled Trials - Kang, Jing-yi; Lei, Shan-shan; Guan, Jin-Tao (Archives of Clinical and Biomedical Research, 2022)
Objective: Liraglutide are associated with a decreased risk of fracture among Type 2 Diabetes Mellitus Patients (T2DM) but the mechanism is unclear, the effect of liraglutide on Bone Mineral Density (BMD) and Bone Turnover Markers (BTMs) were taken into consideration. Method: We searched for randomized controlled trials of liraglutide in PubMed, Embase, the Cochrane Library, Web of Science, CNKI and VIP database up to October 2021. Heterogeneity among studies was examined by Cochrane Q test. Results: 7 pieces of eligible literature involving 478 patients were divided into the liraglutide treatment group (n = 241) and control group (n = 237) in this meta-analysis. Based on fixed effect model, liraglutide had no beneficial effect on BMD (MD: 0.00; 95% CI: (-0.01, 0.02); p=0.69, I2=0%), but there were significant increase effects of liraglutide on bone gla protein (BGP, MD: 0.63; 95% CI: (0.23, 1.03); p=0.002, I2=36%), Bone specific alkaline phosphatase (BAP, MD: 0.85; 95% CI: (0.30, 1.40); p=0.002, I2=23%) and PINP (MD: 6.90; 95%CI: (5.71, 8.09); p =0.002) compared to conventional treatment. Moreover, liraglutide decrease serum β cross-linked C-telopeptide of type I collagen (β-CTX, MD: 0.03; 95%CI: (0.01, 0.05); p = 0.0005, I2 =0%). Conclusions: This meta-analysis demonstrated that liraglutide significantly increase OC, BAP, PINP and reduce β-CTX content compared to conventional treatment in T2DM patients, but the difference was no beneficial effect on BMD. This finding may provide additional evidence for the use of liraglutide to improve skeletal health in T2DM patients.